Pathophysiological Changes of Physical Barriers of Peripheral Nerves After Injury - Liu, Qianyan; Wang, Xinghui; Yi, Sheng (Frontiers in Neuroscience, 2018)
Peripheral nerves are composed of complex layered anatomical structures, including epineurium, perineurium, and endoneurium. Perineurium and endoneurium contain many physical barriers, including the blood-nerve barrier at endoneurial vessels and the perineurial barrier. These physical barriers help to eliminate flux penetration and thus contribute to the establishment of a stable microenvironment. In the current review, we introduce the anatomical compartments and physical barriers of peripheral nerves and then describe the cellular and molecular basis of peripheral physical barriers. We also specifically explore peripheral nerve injury-induced changes of peripheral physical barriers, including elevated endoneurial fluid pressure, increased leakage of tracer, decreased barrier-type endothelial cell ratio, and altered distributions and expressions of cellular junctional proteins. The understanding of the pathophysiological changes of physical barriers following peripheral nerve injury may provide a clue for the treatment of peripheral nerve injury.